Innovative Methods in Mathematics Courses - Jahona Yusupova; Sunnatullo Do'stov (Zien Journals, 2022)
The article analyzes the didactic methods used in mathematics lessons in schools.
Keywords: Classic Pairs; method; Pair-to-pair communication